Determinación del contenido de antioxidantes y actividad antioxidante de placenta de cacao (theobroma cacao l.), variedades clon CCN-51 y tipo nacional x trinitario - Chumaña Zambrano, Oscar Alfredo (2022)
Currently, Ecuador is the territory of a considerable and important source of cocoa production and the great variety of resulting by-products has been a very important raw material economically and culturally for the country for several decades, thanks to the demand for fine aroma cocoa that It has exceptional qualities in aroma and flavor. The growing demand for functional foods and nutritional properties are of general interest by the food and pharmaceutical industry, the first investigations about cocoa beans show a high antioxidant activity that corresponds to its components (polyphenols, flavonoids, carotenoids, anthocyanins, etc. ) since they have the ability to inhibit and even stop the action of free radicals that act by oxidizing and deteriorating the human body. The investigative focus of this work is to objectively determine the presence and antioxidant capacity in the residues (by-products) of the cocoa placenta of two varieties of the National x Trinitario type and Clone CCN-51 through techniques such as ABTS+ (2,2-azinobis-cationic radical 3- ethylbenzothiazoline-6-sulfonic acid) and FRAP (ferric reduction tripyridyltriazine ferric Fe3 –TPTZ). Student's t-test and Pearson's correlation analysis were used to compare content and antioxidant activity. In placenta of the Nacional x Trinitario type variety, values of 235.85 μM TE●g and 227.04 μM TE●g were obtained by means of ABTS+ and FRAP respectively; on the other hand, in the CCN-51 variety 212.72 μM TE●g and 187.47 μM TE●g in the ABTS+ and FRAP analysis techniques respectively. Thanks to Pearson's correlation, it was determined in this study that there is an effect of variety on carotenoid content and ABTS+ antioxidant activity in Nacional x Trinitario type cacao and clone CCN 51. On the other hand, the content of anthocyanins, polyphenols, flavonoids and FRAP antioxidant activity did not present a statistically significant effect according to the varieties analyzed. Keywords: Placenta, waste recovery, antioxidant capacity, free radicals, biorefinery